2020
DOI: 10.1002/agj2.20034
|View full text |Cite
|
Sign up to set email alerts
|

Developing functional relationships between temperature and soybean yield and seed quality

Abstract: Temperatures that vary spatially and temporally over the soybean growing areas affect soybean seed yield and quality. Five day/night temperature, 21/13, 25/17, 29/21, 33/25, and 37/29°C, effects on total biomass, yield, and seed quality parameters were investigated on indeterminate (Asgrow AG5332, AG) and determinate (Progeny P5333RY, PR) soybean cultivars. The cultivar × temperature interaction was significant for total biomass, seed yield, protein, oil, palmitic acid, oleic acid, linolenic acid, raffinose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…Piper and Boote [59] showed variation in protein and fat concentration in 20 soybean cultivars, with protein content significantly dependent only on cultivar, while fat content on cultivar and temperature related to latitude. Further, other authors proved significant effect of genotype on protein [54], fat [55,60,61], ash [61], and carbohydrate (raffinose and stachyose) contents [62]. The results presented in this study showed little anecdotal varietal variation in sugar content, which is consistent with the study of Alsajri et al [55].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Piper and Boote [59] showed variation in protein and fat concentration in 20 soybean cultivars, with protein content significantly dependent only on cultivar, while fat content on cultivar and temperature related to latitude. Further, other authors proved significant effect of genotype on protein [54], fat [55,60,61], ash [61], and carbohydrate (raffinose and stachyose) contents [62]. The results presented in this study showed little anecdotal varietal variation in sugar content, which is consistent with the study of Alsajri et al [55].…”
Section: Discussionsupporting
confidence: 91%
“…Further, other authors proved significant effect of genotype on protein [54], fat [55,60,61], ash [61], and carbohydrate (raffinose and stachyose) contents [62]. The results presented in this study showed little anecdotal varietal variation in sugar content, which is consistent with the study of Alsajri et al [55]. On the other hand, Kozak et al [63] proved that the chemical composition of soybean seeds was more dependent on climatic conditions than on cultivar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pádua et al [14] reported that environmental conditions, and field weather (temperature, rainfall and relative humidity) influence the quality of seeds throughout the growing periods. According to Alsajri et al [17], the interaction between soybean cultivar and temperature influences soluble sugar (glucose, sucrose and raffinose family oligosaccharides (RFOs)) content of the seeds, but the sucrose and raffinose content declined when temperature increased. Soluble sugars are a vital seed constituent, for example, sucrose promotes seed filling, whereas RFOs may increase seed vigor under stressful environments [18].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum and maximum temperatures under baseline were below 20 °C and 31 °C, respectively. These values are within the optimal range for soybean growth (Vu et al, 2001;Alsajri et al, 2020), which reduced impacts of water deficit by the lower water demand (Jumrani and Bhatia, 2018;. However, the future climate projections indicate reduced rainfall and increased air temperature, potentiating yield losses in relation to the baseline under RCP 8.5 in 2041-2070.…”
Section: Discussionmentioning
confidence: 78%